Empowering Minds: A Holistic Approach To Literacy, Numeration, And Technological Adaptability For Innovative Differentiation And Agility - mulyani, sri (Center of Language and Cultural Studies, 2023)
The objective of this study is to examine the impact of literacy, numeracy and technological adaptation on students' agility and competency absorption capacity with differentiated learning innovation as an intervening variable in Surabaya, East Java Province, Indonesia. The study was conducted in Surabaya City, in six sub-districts. The study's sample consisted of 125 respondents. The data obtained from the surveys was further analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Additionally, literacy has a positive and significant effect on the agility of students' ability to absorb competencies, while government numeracy has a positive and significant effect on the agility of students' competency absorption capacity; Technology Adaptability directly has a positive and significant effect on the agility of competency absorption capacity; Differentiated learning innovation directly has a positive and significant effect on competency absorption capacity. Differentiated learning innovation is able to partially mediate literacy, numeracy and technological adaptability on the agility of competency absorption capacity in Serang City, Banten Province. The research findings and data analysis indicate that literacy, numeracy, and technology adaptability have a direct and significant impact on differentiated learning innovation.